Geographic distribution of burn in an Australian setting - Randall, Sean; Wood, F.; Boyd, J.; Duke, J. (Pergamon Press, 2017)
Objective: To investigate the geographic distribution and temporal trends of burn admissions in an Australian setting. Methods: Health administrative data of all persons hospitalised for a first burn in Western Australia for the period 2000–2012 were used. Crude and standardised incident rates were generated for each region. Maps of crude rates were generated for state regions and postcode-suburbs of Perth, the capital city. Standardised incidence rates were generated for Western Australia, total and regions, and for sub-cohorts defined by age (<20 years; ≥20 years), TBSA burn severity and major causes of burns (fire, scalds and contact). Negative binomial regression was used to examine temporal changes and generate incidence rate ratios (IRR) with 95% confidence intervals (CI). Results: Perth had the lowest burn admission rate per population; clusters of suburbs of lower social advantage and higher immigrant settlement were identified as being at high risk. While the highest observed admission rates were found in Kimberley and Goldfields (remote) regions, after adjustment for the regional demographic structures, the Wheatbelt and Mid-West (rural) regions were found to have the highest adjusted rates of burn admissions. Significant annual declines in admission rates were found for the Kimberley, Pilbara and Goldfields (remote regions); however, stable admission rates were identified for all other regions. Conclusions: The Mid-West and Wheatbelt rural regions were found to have the highest risk of burn admissions raising concerns about farming-related injury. Safety awareness and burn prevention strategies need to be continued, with specific attention to these high risk areas, to reduce burn admissions in Western Australia.